Politik Sebagai Tanggung Jawab: Konstruk Pemikiran Tokoh Muslim Abad Pertengahan - Ridhatullah Assya’bani (JURNAL AT-TURAS, 2019)
The political discourse is indispensable from the human life. In terms of Islamic teaching, it implies a relation among individuals, or between individual and society, or among societies in order to be a basic value of solidarity building. Consequently, politics became a raison de etre for those who had primordial responsibility to the others. This article is to portray the Middle Age Muslim thinkers’ arguments and their basic epistemologies on politics as responsibility. They argued partly that human being need the others to be shared living, and it was necessary to be ‘political’ with building a community. Furthermore, a political human being need to be responsible for what they deserve to do to the others.Keywords: human, relation, politics, responsibility